Revision of the genus Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorini) Revisão do gênero Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorini) - Geovan H. Corrêa; Lúcia M. Almeida (Revista Brasileira de Entomologia, 2010)
Harpasus Mulsant, 1850 was studied based on the morphology of the exoskeleton and genitalia. The type material of Harpasus aureus Almeida & Carvalho, 2006, H. quadrifolium González, Corrêa & Almeida, 2008 and a homotype of H. zonatus (Mulsant, 1850) were examined. The lectotype of H. eversmanni (Mulsant, 1850) was designated and two new species were described, Harpasus unifasciatus sp. nov. (Teresópolis, RJ, Brazil) and Harpasus ferrugineus sp. nov. (Puerto Carreño, Vichada, Colombia). Herein a diagnosis for the genus and its seven species, identification key and information about biological aspects are presented. Harpasus Mulsant, 1850 foi estudado baseado na morfologia do exoesqueleto e genitália. O material tipo de Harpasus aureus Almeida & Carvalho, 2006, H. quadrifolium González, Corrêa & Almeida, 2008 e o homótipo de H. zonatus (Mulsant, 1850) foram examinados. O lectótipo de H. eversmanni (Mulsant, 1850) foi designado e duas novas espécies foram descritas, Harpasus unifasciatus sp. nov. (Teresópolis, RJ, Brasil) e Harpasus ferrugineus sp. nov. (Puerto Carreño, Vichada, Colômbia). São apresentadas diagnoses detalhadas para o gênero e suas sete espécies, chave de identificação e informação sobre aspectos biológicos.